Factors influencing Generation Z's intention to purchase sustainable clothing products in Vietnam. - Thi Thuy An Ngo; Chi Hai Vo; Ngoc Lien Tran; Khanh Vy Nguyen; Thanh Dat Tran; Yen Nhi Trinh (PLoS ONE)
The increasing awareness of environmental challenges has significantly influenced consumer behavior, with sustainable products, particularly sustainable clothing, becoming a top priority for Generation Z consumers. This study aims to investigate the factors influencing Generation Z's purchase intentions toward sustainable clothing in Vietnam, guided by the Stimulus-Organism-Response (SOR) model and Theory of Planned Behavior (TPB) frameworks. Specifically, it examines the effects of green perceived value, green perceived quality, perceived price, social influence, product design, environmental concern, and environmental knowledge on purchase intentions. The study also explores the mediating roles of environmental attitude and product attitude in these relationships. The research employed a quantitative approach, using a Likert scale questionnaire to gather data from 641 Vietnamese Generation Z consumers. The study utilized exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modeling (SEM) to analyze the data. The results revealed that all proposed hypotheses were supported, indicating that all factors significantly impact environmental attitude and product attitude, which, in turn, influence purchase intention. The results emphasize the strong mediating role of environmental attitude and product attitude, suggesting that consumers with positive attitudes toward the environment and products are more likely to intend to purchase sustainable clothing. This research provides valuable insights into the psychological and contextual factors that influence Generation Z's sustainable consumption behavior. For marketers, these findings underscore the need to promote transparency in sustainable practices, emphasize high product quality and appealing designs, and engage this demographic through community involvement and authentic sustainability efforts.